Alteration in humoral immunity is common among family members of patients with common variable immunodeficiency - (:unkn) unknown (ESMON Publicidad S.A., 2014)
Background: The prevalence of primary immunodeficiency (PID) in the relatives of patients with common variable immunodeficiency (CVID) and IgA deficiency is high. Allergic disorders have been recorded in patients with humoral immunodeficiency. We aimed to determine the frequency of humoral immunodeficiency and atopy in the relatives of patients with CVID.Methods: The study population comprised 20 CVID patients and their relatives. All relatives were screened using a questionnaire covering demographic characteristics, warning signs of PID (adults and children), and core questions on asthma, rhinitis, and eczema from the International Study of Asthma and Allergies in Childhood (ISAAC). We also recorded absolute neutrophil and lymphocyte counts, serum immunoglobulin levels, pulmonary function values, and skin prick test results.Results: The study sample comprised 20 patients with CVID (15 males, 5 females; mean [SD] age, 16.4 [9] years) and 63 first-degree relatives (18 mothers, 16 fathers, 16 sisters, 10 brothers, and 3 offspring). The rate of parental consanguinity was 75%. Of 17 family members with positive PID warning signs, 6 had concomitant hypogammaglobulinemia (3 low IgM levels, 2 selective IgA deficiency, and 1 partial IgA deficiency). The ISAAC questionnaire revealed allergic rhinitis in 3 mothers, asthma in 2 fathers, and 1 sibling. Skin prick testing revealed sensitization to aeroallergens in 31.6% of cases in addition to 1 parent and 1 sibling.Conclusions: Almost half of the 20 families with a CVID patient had at least 1 additional member with hypogammaglobulinemia, leading us to recommend routine screening for relatives of CVID patients. © 2014 Esmon Publicidad.
Keywords: Allergy; Common variable immunodeficiency (CVID); Consanguinity; Family screening; Hypogammaglobulinemia; Immunoglobulin A (IgA) deficiency